2012
DOI: 10.4049/jimmunol.1102310
|View full text |Cite
|
Sign up to set email alerts
|

Role of C3a Receptors, C5a Receptors, and Complement Protein C6 Deficiency in Collagen Antibody-Induced Arthritis in Mice

Abstract: The complement system, especially the alternative pathway (AP), plays essential roles in the induction of injury in collagen antibody-induced arthritis (CAIA) in mice. The goal of the current study was to directly compare the roles of receptors for C3a and C5a, as well as the membrane attack complex (MAC), as effector mechanisms in the pathogenesis of CAIA. Clinical disease activity (CDA) in C3aR−/−, C5aR−/−, and C6 deficient (C6-def) mice was decreased by 52%, 94%, and 65%, respectively, as compared with WT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 49 publications
4
102
0
Order By: Relevance
“…Together, these data demonstrate that one mechanism of action of anti-mC5aR may be through reduction of myeloid cell influx into the joint, which is in agreement with the known function of C5a as a potent chemotactic factor. Reduced numbers of infiltrating myeloid cells have been demonstrated in C5aR-deficient mice in the CAIA model and after 10 days of treatment in anti-C5 mAbtreated mice in the CIA model, but again our data are the first to demonstrate that this is an early effect of C5aR blockade [21,22,24]. Part of the reduced levels of inflammatory mediators may be secondary to the reduced myeloid cell infiltration, but this does not rule out that C5a also activate infiltrated cells directly and induce the level of inflammatory mediators and chemokines.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Together, these data demonstrate that one mechanism of action of anti-mC5aR may be through reduction of myeloid cell influx into the joint, which is in agreement with the known function of C5a as a potent chemotactic factor. Reduced numbers of infiltrating myeloid cells have been demonstrated in C5aR-deficient mice in the CAIA model and after 10 days of treatment in anti-C5 mAbtreated mice in the CIA model, but again our data are the first to demonstrate that this is an early effect of C5aR blockade [21,22,24]. Part of the reduced levels of inflammatory mediators may be secondary to the reduced myeloid cell infiltration, but this does not rule out that C5a also activate infiltrated cells directly and induce the level of inflammatory mediators and chemokines.…”
Section: Discussionsupporting
confidence: 69%
“…Together, KC, MCP-1 and MCP-5 have the potential of recruiting a panel of inflammatory cells such as neutrophils, monocytes, macrophages, dendritic cells and lymphocytes into inflammatory sites [41,42]. Reduced levels of MPO, TNF-α, IL-1β, MMP-3 and MIP-1a, MIP-2 have been demonstrated in C5aR-deficient mice in the collagen antibody-induced arthritis (CAIA) model, but our data are the first to demonstrate that this is an early therapeutic effect of C5aR blockade [21,24]. Immunohistochemical stainings demonstrated a reduced influx of neutrophils and macrophages in paws 48 h after single-dose treatment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This suggests that, in the chronic phase of inflammation, where monocyte/macrophage responses become more predominant over neutrophils, C3a may indeed act as a classical proinflammatory mediator. This view is supported by evidence that C3ar1 2/2 animals have modest pathology reductions in chronic disease models, such as rheumatoid arthritis (40). In contrast to the effects of C3a on purified monocytes (39), in vitro investigations into the effects of C3a on LPSinduced cytokine release by PBMCs demonstrate differences in action depending on the phenotype of the cell.…”
Section: C3a Activity On Immune Cellsmentioning
confidence: 97%
“…A vaccine that induces generation of anti-C5a antibodies has been shown to be effective in murine collagen-induced arthritis (CIA) in mice [16], and oral treatment with a small molecule C5a antagonist reduced joint damage in the rat antigen-induced arthritis model [17]. In several mouse models of arthritis C5aR-deficient mice show reduced disease development [18][19][20][21]. In human C5aR knockin mice, a mouse anti-human C5aR monoclonal antibody effectively ameliorated neutrophil-dependent K/B Â N serum transfer-induced arthritis [22], and it has been shown that antimouse C5aR mAb lowers disease activity when administered in the early stages of murine CIA [23].…”
Section: Introductionmentioning
confidence: 99%